Names we call home : autobiography on racial identity - Thompson, Becky W.; Tyagi, Sangeeta (Routledge, 1996)
Names We Call Home is a ground-breaking collection of essays which articulate the dynamics of racial identity in contemporary society. The first volume of its kind, Names We Call Home offers autobiographical essays, poetry, and interviews to highlight the historical, social, and cultural influences that inform racial identity and make possible resistance to myriad forms of injustice.